PENGUATAN UMKM TERASI DI DESA JEROWARU, LOMBOK TIMUR, MELALUI LEGALITAS HALAL DAN NIB - Setiawan, Ketut Dharma Putra; Elniawati; Huzzaema, Fathin Husna; Putra, Risky Ananda; Wulandari, Amilia; Salida, Baiq Mila; Damayanti, Apriatun; Sartika, Rintihani Lodia Maya; Kinanti, Intan Alia; Imtihan, Zahrul; Larasati, Chandrika Eka (Universitas Mataram, 2025)
Community Service Program (KKN) is a form of education that provides direct learning experiences to students to identify and address community problems, while enhancing the relevance of higher education to development needs. The shrimp paste (terasi) Micro, Small, and Medium Enterprises (MSMEs) in Jerowaru Village, East Lombok, possess significant economic potential but face business legality challenges, particularly concerning Business Identification Numbers (NIB) and Halal Certification. This activity was conducted in Jerowaru Village during July-August 2025 through direct socialization and assistance to terasi MSME actors in obtaining NIB via the Online Single Submission (OSS) system and applying for Halal Certification through the SiHalal system. The results indicate an increase in MSME actors' understanding and awareness of legality's urgency, with several MSMEs successfully obtaining NIB and/or submitting Halal Certification applications, leading to enhanced consumer trust and potential market expansion. Nevertheless, technical issues with online systems and data completeness remain challenges. It is concluded that legality assistance by KKN students significantly contributes to increasing the capacity and competitiveness of terasi MSMEs in Jerowaru Village, simultaneously bridging gaps in government policy implementation.